Diagnóstico do estilo de aprendizagem do aluno a partir de ferramentas de comunicação - Hoehstein, Gilcimar; Kemczinski, Avanilde; Gasparini, Isabela; Pimenta, Marcelo S. (Cadernos de Informática, 2011)
Adaptive Hypermedia Systems are systems that adapt themselves according to the user’s profile. They are used in distance learning environments to adapt teaching materials and navigation to the user´s learning preferences. These systems support the learning process in a personalized manner, and they can be adapted to the Cognitive Learning Style (CLS) of each individual. This paper presents a diagnostic tool to the student's CLS active x Reflective dimension of Felder and Silverman’s model based on user´s interaction with asynchronous communication tools.